Mixed Reality Images Trilogy of Synthetic Realities III - Grabbe, Lars C.; Rupert-Kruse, Patrick; Schmitz, Norbert M. (Yearbook of Moving Image Studies, 2023)
The interplay of physical reality and digital media technologies is getting enhanced by new interfaces. The age of hyper-reality turns into the age of hyper-aesthetics and immersive image technologies - like mixed reality - enable a completely novel form of interaction and user relation with the virtual image structures, the different screen technologies, and embedded physical artefacts for interaction. »Mixed Reality Images« contributes to the wide range of the hyper-aesthetic image discourse to connect the concept of mixed reality images with the approaches in modern media theory, philosophy, perceptual theory, aesthetics, computer graphics and art theory as well as the complex range of image science. This volume monitors and discusses the relation of images and technological evolution in the context of mixed reality within the perspective of an autonomous image science.